Facile Heck coupling synthesis and characterization of a novel tris(4-(pyridine-4-vinyl)phenyl)methylsilane tridentate core - Bull, Okpara Sergeant; Don-Lawson, Chioma (European Journal of Chemistry, 2024)
Aromatic rigid ligands with carboxylate, phosphate, or pyridyl terminals are highly important today for application in the manufacturing of metal-organic frameworks (MOFs), covalent organic frameworks (COFs), and other supramolecular structures. Aromatic rigid ligands give rigidity to MOFs and COFs materials. In addition, building units are important in that their judicious selection can result in a 2-D or 3-D framework with moderate or high surface area. Most aromatic linkers are based on carbon centres which are associated with a negative impact on the environment. However, in contrast, silicon-based centres are scarce and benign to the environment, even though they can be prepared facilely via metathesis. Here, we report the facile preparation of a new tris (4-(pyridine-4-vinyl)phenyl) methylsilane using the classical Heck coupling reaction. The bridging ligand was synthesized via the standard Heck coupling of 4-vinylpyridine with tris(4-bromophenyl)(methyl)silane.